A Rare Presentation of a Common Disease: A Diagnostic Dilemma - Somnath Maitra; Sk Adnan Yusuf; Koushik Ray; Rahul Singla; Jiban Krishna De; Subhadeep Basu (International Journal of Medical Research and Review, 2022)
Malaria affects millions of people across the globe .The classical clinical features may be absent, but the rapid diagnosis helps in early treatment and thus avoids complications .We present a case of co infection of Plasmodium  vivax and Plasmodium falciparum malaria in a female patient presenting with fever and pain abdomen and incidental detection of splenic infarct .The co infection  is uncommon and treatment should target both to avoid complications . Also,  the exact pathogenesis is un known and though splenic infarct is uncommon and missed due to lack of symptoms , it should be followed up.